Adaptasi Bahasa dan Budaya dari Skala Kepribadian Big Five - Neila Ramdhani (Jurnal Psikologi, 2012)
The use of Big Five Personality taxonomy in research about personality day by day keeps increasing. In Indonesia, the Big Five personality Inventory (BFI) is utilized to predict consump¬tive behaviors, entrepreneurship interest, consumers’ satisfaction and organizational commitment. The inventory used in such research is varied with names of both Big Five and Five Factor Model, consisting of 44 aitems, 50 aitems, 100 aitems, or even 300 aitems. This research aims to adapt linguistically and culturally the aitems of BFI of Oliver John’s 44 aitems version.Two steps of research will be reported in this article, namely Adaptation of BFI into Indonesian and Testing of Indonesian version of BFI. The subjects of this research are 961 people with diverse range of age, education and place of origin. The results of the step 1 are presented in the form of a description of language and cultural adaptation processes. The validity of every dimension of BFI will be calculated by correlating the score of each aitem with the total score, whereas the reliability is achieved through conducting Alpha Cronbach test. A factor analysis of the data obtained is also done to find out the amount of the Indonesian-version BFI factors. Keywords: Big Five Inventory, cultural translation, language, personality traits